Unidad especial de rehabilitación física (2019)
The following work talks about the problematic and possible consequences of the Bogotá-Girardot urban line, a special analysis is done to solve the problems encountered. It starts from the general study of the line, continues with the urban aspect at the master plan level, then proposes a solution at the municipal level at the partial plan level and ends with an architectural project that will be part of an architectural volume network that will solve the general problem of the broker.